Service Quality Insights from Online Reviews of Four-Star Hotels - Echo Perdana Kusumah; Iza Guspian (Goodwood Publishing, 2026)
Purpose: This study analyzes tourists’ perceptions of service quality in four-star hotels on Bangka Island, Indonesia, using Aspect-Based Sentiment Analysis (ABSA) of online reviews to identify key service aspects and sentiment patterns for evidence-based hospitality management. Research Methodology: A quantitative text-based research design employing text-mining techniques was applied. A total of 5,576 online customer reviews were collected from Google Reviews and analyzed using a lexicon-based aspect-based sentiment analysis (ABSA) approach. The analysis involved text preprocessing, aspect extraction through keyword mapping, and sentiment polarity classification into positive, neutral, and negative categories across multiple service dimensions, including staff service, cleanliness, room comfort, food and beverages, location, and price. Results: The analytical results demonstrate predominantly positive tourist perceptions of all service aspects of four-star hotels on Bangka Island. Staff service, cleanliness, and location achieved the highest levels of positive sentiment, underscoring their importance in shaping customer satisfaction. In contrast, price and food and beverage services exhibit relatively higher proportions of negative sentiments, reflecting concerns related to perceived value for money and dining experiences. Conclusions: Overall, four-star hotels on Bangka Island largely meet tourists’ service quality expectations; however, improvements in pricing strategies and food and beverage offerings are necessary to enhance perceived customer value. Limitations: The analysis was limited by the use of a lexicon-based sentiment approach and reliance on a single online review platform. Contributions: This study reinforces the applicability of lexicon-based ABSA for analyzing informal hospitality reviews and provides practical, data-driven insights for hotel managers and destination stakeholders.